“120 out of 60”: practices and attitudes of workers towards animals in a Portuguese slaughterhouse - Fonseca, R. P. (Sociologia, Problemas e Práticas, 2019)
This study aims to understand the practices and attitudes of workers that deal with animals in a slaughterhouse. For this purpose, it was used photographic documentation during the “routing”, “stunning”, “hanging” and “bleeding” of animals in the slaughter line; also the method of qualitative analysis that required interviewing to eight individuals: two women and six men. Although workers recognize animals as sentient beings, the operationalization of their tasks in the slaughter line is dependent on strategies that require objectification and emotional distancing. Conflicting attitudes related to certain species of animals were also evidenced. Labor context (slaughterhouse), time spent, the performed tasks, animal species, particularly gender and socio-cultural trajectories of workers stood out as predominant factors that influenced their practices and attitudes.